Incidence, causative organisms, and risk factors of bloodstream infections in pediatric liver transplant patients: a systematic review - Mohamad Shieb; Rand Hasanain; Zara Arshad; Faisal A. Nawaz; Rahul Kashyap; Eric J. Stern (The Korean Pediatric Society, 2024)
Bacterial bloodstream infections (BSI) are the leading cause of mortality and morbidity in pediatric solid organ transplant recipients. This systematic review aimed to pool global data from leading transplant institutions and identify the overall incidence, risk factors, and causative organisms of BSI in pediatric liver transplant recipients. A systematic review of the PubMed and OVID databases was conducted from 2000 to 2022. The initial search yielded 252 unique articles, which were independently reviewed by 2 authors. Articles that reported pediatric-specific data on BSI in isolated liver transplant patients were included, including the incidence of BSI, isolated organisms, and involved risk factors involved. This systematic review was registered with PROSPERO (ID: CRD42023403206). Fourteen articles from the United States, France, Iran, Japan, Korea, South Africa, Thailand, and Turkey were included. A total of 4,812 liver transplants were included in the final analysis. The mean patient age was 25 months (age range, 0-18 years), and 50.9% were male. The overall incidence of BSI was 23.5% (range, 14.7%-55%). The most commonly reported organisms were Staphylococcus epidermidis, Enterococcus, Klebsiella spp., and Escherichia coli. Among the risk factors studied, postope rative biliary complications, a medical history of biliary atresia, and younger age were the risk factors most commonly associated with BSI. Bacterial BSI after pediatric liver transplantation occur at a high incidence, with a unique organism profile notable for a higher percentage of gram-negative organisms. Further studies are required to de-termine the most appropriate prophylactic and empirical antibiotic management strategies for this population.